Assessment of cognitive–motor functions in adults with perceived neuropsychological problems using NIH toolbox after remote biofield energy treatment as non‐pharmacological intervention: A randomized double‐blind placebo controlled trial - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Sambhu Mondal; Snehasis Jana (Neuropsychopharmacology Reports)
Abstract Non‐pharmacological interventions include physical activity, biofield energy therapy, reiki, Tai chi, and therapeutic touch. However, no reports analyzed the effectiveness of biofield therapy on cognition and motor function performance in adult subjects. The study aimed to investigate the impact of remote biofield energy healing therapy on cognition and motor functioning in adults with self‐perceived neuropsychological impairments. This was a randomized double‐blind clinical trial that involved 114 participants with self‐perceived neuropsychological impairments. The participants were divided into three groups (control, sham control, and biofield intervention). Cognitive and motor function scores were assessed using the NIH Toolbox at baseline (day 0), day 90, and day 180. The biofield treatment group showed significant improvements in language function (p < 0.0001), working memory (p < 0.0001), and episodic memory (p < 0.0001) scores. Other cognitive functions also improved, although not statistically significant. The biofield intervention group also demonstrated significant enhancements (p < 0.05 to p < 0.0001) in locomotion, standing balance, dexterity, grip strength, and muscle endurance. No adverse effects were reported. The results suggest that remote biofield energy therapy is a safe, noninvasive intervention that improves cognitive and motor functions in adults. Further research is needed to understand its clinical benefits.